Meningkatkan Minat Dan Prestasi Belajar Metode PBL Berbantuan Mind Mapping Yang Kreatif Materi Makna Dan Paham Gereja Kelas XI SMA Bruderan Purwokerto - Stephanus Dwi Rossanto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
There is a problem that in the class of SMA Bruderan Purwokerto, it is found that students feel bored and bored because of the monotonous method. Attention, interest, and enthusiasm for student learning is low, so that the percentage of completeness only reaches 60% (KKM = 70). The problem is the learning process does not involve students from SMA Brudrean Purwokerto. This research is a Research Methodology with research subjects being students of Class XI IPA 2. consisting of 7 female students and 8 male students. This study was designed by looking at the results of student achievement in the Experiment class with the Creative Mind Mapping Assisted Problem Based Learning Method. which will be compared with the learning achievement of students in the Control class, so it can be seen that the Problem Based Learning Method Assisted by Creative Mind Mapping. is one alternative that can increase student interest and achievement in achieving completeness. In addition, educators themselves and colleagues will be able to create learning that involves students in an active, communicative and fun way. Finally, with the Problem Based Learning Method Assisted by Creative Mind Mapping it increases student interest and achievement with student learning outcomes above the KKM of 70.